Association of major dietary patterns with socioeconomic status, obesity, and contracting COVID-19 among Iranian adults - Maharat, Maryam; Rahimlou, Mehran; Sioofi, Ali; Sajjadi, Seyedeh Forough; Moosavian, Seyedeh Parisa (Frontiers in Nutrition, 2024)
Background The coronavirus disease 2019 (COVID-19) pandemic clearly affected the lifestyle and dietary habits of millions of people worldwide. The purpose of this study was to evaluate the association of major dietary patterns with socioeconomic status, obesity, and contracting COVID-19. Methods We conducted a cross-sectional study using an online survey for data collection with a total of 1,187 participants (over the age of 18 years) who reported their sociodemographic details, anthropometric index (weight and height), and dietary intake. Multivariable logistic regression models were applied to assess the association between major dietary patterns and study outcomes. Results A total of 1,106 adults were included in the current analysis. We identified three major dietary patterns (plant-based, meat, and Western dietary patterns). The mean age of participants was significantly higher in the upper tertile of plant-based dietary patterns (DPs) compared to the first tertile, while it was lower in the top tertile of meat and Western DPs. The percentage of participants who lived in urban areas was significantly higher in the third tertile of meat DP than in the first tertile (p < 0.001). Moderate adherence to Western DP was significantly associated with increased odds of obesity (OR: 1.79; 95% CI: 1.17, 2.74). In addition, high adherence to Western DP was significantly related to increased odds of obesity after controlling for confounders. Subjects in the second tertile of the Western DP had higher odds (95% Cl: 1.04, 1.92) for COVID-19 infection than the first tertile. Conclusion This study showed that moderate and high adherence to a Western dietary pattern was associated with a higher risk of obesity and COVID-19 infection during the pandemic. Future studies are needed to confirm these findings.